2018
DOI: 10.18203/2394-6040.ijcmph20180256
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in developmental assets profile of college going youth: a report from India

Abstract: Background: Recent years have seen a paradigm shift in the way development during young age is considered where the focus of attention has moved from the deficit based approaches to one that of strength based. Among the various strength based approaches in youth development, developmental assets profile has achieved a prominent place. The present study is aimed at providing a preliminary evaluation of developmental assets on a group of young people from Kerala State, India. Methods: One hundred and forty (63 f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Previous evidence has shown that there are gender differences in developmental assets, self-control, and IGD. In a study of Indian youth, significant gender differences were found in both internal and external developmental assets (54). Similarly, Portuguese boys and girls experienced different developmental assets (55).…”
Section: Gender As a Potential Moderatormentioning
confidence: 98%
“…Previous evidence has shown that there are gender differences in developmental assets, self-control, and IGD. In a study of Indian youth, significant gender differences were found in both internal and external developmental assets (54). Similarly, Portuguese boys and girls experienced different developmental assets (55).…”
Section: Gender As a Potential Moderatormentioning
confidence: 98%